2010
DOI: 10.1177/102490791001700307
|View full text |Cite
|
Sign up to set email alerts
|

Incarcerated Inguinal Hernia in Children

Abstract: The aim of this study was to document the data of incarceration in a group of children with inguinal hernia and to investigate whether incarceration could have been prevented. Materials and methods: A retrospective study reviewed the records of 3100 children who underwent herniorrhaphy between 1989 and 2007 in one centre, with 113 patients having hernia incarceration. In 16 patients, manual reduction was not attempted because of signs of strangulation, and in the remaining ones, reduction following sedation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This is comparable to previous reports. [3,8,14] In a comparative study, Lawal et al [16] observed that infants are three times more likely than older children to develop complicated hernia. This has underlined the high risk of complicated hernias in infants and as such has brought to fore the need for early elective surgery, particularly in this category of children.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is comparable to previous reports. [3,8,14] In a comparative study, Lawal et al [16] observed that infants are three times more likely than older children to develop complicated hernia. This has underlined the high risk of complicated hernias in infants and as such has brought to fore the need for early elective surgery, particularly in this category of children.…”
Section: Discussionmentioning
confidence: 99%
“…[3,9] Once an incarcerated hernia is reduced, a delay of 24-48 h is necessary to allow resolution of edema of the content of the hernial sac. [8,9] This study highlights our experience in the management of incarcerated indirect inguinal hernia in children in a tertiary care hospital in Southwest Nigeria.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…They present with a tense, tender, irreducible lump in either groin and sometimes associated with vomiting 1,2,3 . About 95% of incarcerated inguinal hernias may be reduced successfully by nonoperative maneuvers of manual reduction called taxis under sedation 4,5,6,7,8,9,10,11 . This study describes our experience of incarcerated inguinal hernia over a period of 30 months at the department of paediatric surgery in Kanti Children's Hospital.…”
mentioning
confidence: 99%